STORY THEATRE AND THE COMMUNICATION OF ADOLESCENT SEXUAL AND REPRODUCTIVE HEALTH: THE RAPE OF WOMANHOOD IN CALABAR, NIGERIA - Merab Yta, Edisua; Idegu, Emmy Ikanaba Unuja (Universitas Negeri Makassar, 2020)
Young people in Calabar have diverse sexual and reproductive health challenges. Many argue that integrating gender into health programming will help reduce some of these issues because gender is central to shaping many sexual and reproductive health issues. This study used story theatre, as a qualitatively, narrative and participatory approach in trying to understand how gender relates to and influences adolescent sexual and reproductive health. Twenty story sessions were held for a hundred young people (aged 10-19) in four selected communities’ Akai Effa, Ikot Ekpo, Efut Uwanse and Nyakassang all situated in Calabar Municipality and Calabar South Local Government Areas of Cross River State, South-South Nigeria. Sessions were recorded and later coded and analyzed for sexual and reproductive health as well as gender themes. Key findings revealed that rape and gender-related sexual assault and violence, teenage pregnancy, intergenerational as well as the objectification of women ranked amongst the highest Adolescent Sexual and Reproductive Health (ASRH) and gender issues in the communities. Young females seem to be getting more of the negative effects than boys because they are seen as pleasurable and economic assets. It is recommended that out of the box approaches which will involve multi-systems and stakeholders be used in finding a solution to this worrisome issue.